Research on the Flame-Retardant Performance of Antioxidant Gel Foam in Preventing Spontaneous Coal Combustion - Hu Wen; Ziqi Wang; Maoxia Liu (Fire, 2025)
Antioxidant gel foams are promising materials for coal mine fire prevention due to their unique physicochemical properties. To address the limitations of conventional suppression methods under high-temperature conditions, this study investigates a newly developed antioxidant gel foam and its mechanism in inhibiting coal spontaneous combustion. A novel antioxidant gel foam was formulated by incorporating TBHQ and modified montmorillonite into a sodium alginate-based gel system. This formulation enhances the thermal stability, water retention, and free radical scavenging capacity of the gel. This study uniquely combines multi-scale experimental methods to evaluate the performance of this material in coal fire suppression. Multi-scale experiments, including FTIR, leakage air testing, programmed temperature rise, and small-scale fire extinction, were conducted to evaluate its performance. Experimental results indicate that the antioxidant gel foam exhibits excellent thermal stability in the temperature range of 200–500 °C. Its relatively high decomposition temperature enables it to effectively resist structural damage in high-temperature environments. During thermal decomposition, the gel releases only a small amount of gas, while maintaining the integrity of its internal micro-porous structure. This characteristic significantly delays the kinetics of coal oxidation reactions. Further research revealed that the spontaneous combustion ignition temperature of coal samples treated with the gel was significantly higher, and the oxygen consumption rate during spontaneous combustion was significantly reduced, indicating that the gel not only effectively suppressed the acceleration of the combustion reaction but also significantly reduced the release of harmful gases such as HCl. Scanning electron microscope analysis confirmed that the gel maintained a good physical structure under high temperatures, forming an effective oxygen barrier, which further enhanced the suppression of coal spontaneous combustion. These findings provide important theoretical and practical guidance for the application of antioxidant gel foams in coal mine fire prevention and control, confirming that this material has great potential in coal mine fire safety, offering a new technological approach to improve coal mine safety.